Integracija/inkluzija otrok z motnjo sluha - Schmidt, Majda (Šolsko polje, 2007)
The article presents some charaeteristics of integration/inclusion of children with hearing impairments, conditions for its implementation, learning opportunities and different approaches toward organizational support in our educational system. International research results on academic and social-emotional achievements of students with hearing impairments have shown positive and negative outcomes of inclusion. Since integration/inclusion has already been implemented in our country for a few years, it is a high time we directed basic research attention to the investigation of direct practice, as well as to the existing obstacles and barriers which hinder participation and learning of students within the school system.
Keywords: defektologija; inkluzija; integracija; otroci s posebnimi potrebami; slušne motnje; vzgoja in izobraževanje